Pengembangan Aplikasi Web Sebagai Media Informasi Dan Sistem Pencatatan Data Pelanggan Pada Layanan Tour Guide Trip Asia - Satria Mandala; Rajiv Dharma Mangruwa; Bramantya Hendrawan Yoga; Imam Arif Wicaksono; Adika Ghivan Pratama; Muhammad Ardiansyah Pratama; Deven Febrian Susilo (CV. Multi Kreasi Media, 2026)
This community service activity aimed to assist Solo Tour Guide Specialist, a tourism guide service MSME under the HalloTrip brand, in strengthening digital promotion and organizing customer data recording. Before the activity, service information was still shared through WhatsApp and personal networks, while the partner did not yet have an official public information platform. As a result, business profiles, travel packages, testimonials, schedules, and booking channels were not presented in a centralized manner. The solution developed consisted of two web-based systems: a public landing page as a tourism service information showcase and an admin website for customer data recording. The systems were developed using HTML, CSS, JavaScript, and Tailwind CSS through a participatory approach with the partner. The activity workflow covered needs identification, interface design, system development, functional testing, training, mentoring, and evaluation. The outcome was the HalloTrip website, accessible at hallotrip.vercel.app, featuring Asian destination information, testimonials, a real-time weather widget, a WhatsApp booking button, and an admin website with login and customer data recording features. The socialization session was conducted online so that the partner could understand the website workflow and use the system more independently. Partner feedback showed very positive acceptance, with four main indicators receiving full agreement in the agree and strongly agree categories. Although 25% neutral responses appeared in the committee service aspect, the overall solution was considered relevant and practical as an initial step in digitally transforming the partner's promotion and administration.